Distributed Client/Server Architecture With Dynamic Middle Tier - Choong, Khong Neng (1999)
Widespread use of computer networks and the demanding needs of current network applications and technology impose a challenge to use the bandwidths in an efficient manner so as to solve the network congestion and server overloading problems. Some past and on-going solutions such as server replications and caching have been proposed to overcome these deficiencies. However, these solutions have not been implemented in an economical and configuration-transparent manner. Moreover, the problems of caching and disseminating real-time multimedia data in a bandwidth-conservative manner have not been addressed. In this thesis, a CHEK Proxy Framework (CPF) has been developed using a proxy solution to address these problems. By caching, proxy has become a traditional solution in reducing user-perceived latency and network resource requirements in the network. CPF helps to create a middle-tier application platform proxy transparently and dynamically in the client sub-network to execute the sharable section of any server application codes. This is as the application proxy. Besides caching static web contents, this local application proxy helps to deliver real-time multimedia data on behalf of the remote server with lower bandwidth and better performance. CPF helps to minimize WAN connections while maximizing LAN interactions by multiplexing and de-multiplexing client requests through to the server via the proxy. As a result, the central server is made more reliable and scalable. The monitoring and management of the CHEK distributed objects is also made easier through the use of the CHEK Management Console (CMC). CMC displays the inter-relationships between the distributed objects and their status information on a GUI-based control panel for ease of management. With its dynamic and transparent features, software verslOrung and maintenance problems are readily overcome. CPF has been shown to be useful in most client/server applications, particularly those of broadcasting and collaborative nature such as video broadcastings and chat systems. CPF solves the network congestion and server overloading problems with the presence of a middle-tier proxy application platform which is allocated in the client sub-network with no manual configurations.